Adherence to Atrial Fibrillation (AF) Better Care (ABC) pathway and adverse clinical outcomes in patients with atrial fibrillation - Mohammad Ammar Hakim Osman; Izzati Abdul Halim Zaki; Sahimi Mohamed; Muhammad Asyraf Harun; Raja Ezman Faridz Raja Shariff; Long Chiau Ming; Hanis Hanum Zulkifly (Heliyon)
Introduction: The Atrial Fibrillation Better Care (ABC) pathway was introduced to improve the management of patients with atrial fibrillation (AF) thus improving their outcomes. However, adherence to the ABC pathway has been found to be suboptimal in many studies. Objective: To investigate the prevalence and factors associated with adherence to the ABC pathway, and subsequent adverse clinical event. Methods: Patients with AF from two cardiology centers within June 2020 to December 2022 were included in this retrospective cohort study. Adherence to “A”: optimal time in therapeutic range (TTR) > 65 % for warfarin therapy and appropriate dosage of non-vitamin K antagonist oral anticoagulants (NOACs) prescribed, “B”: attainment of an European Heart Rhythm Association (EHRA) score 1–2 and “C”: appropriate management of underlying cardiovascular (CV) disease. Thromboembolic (TE) event is defined as suffering ≥1 stroke and/or transient ischemic attack. Results: A total of 322 AF patients [mean age: 70 ± 12 years; 47.5 % female] were followed for a mean 22 ± 1 months. Only 90 (28 %) patients were managed according to the ABC pathway while 232 (72 %) patients were non-adherent to the ABC pathway. Adherence to A, B and C, and overall ABC pathway was observed in 227 (70.5 %), 321 (99.7 %), 128 (39.8 %) and 90 (28 %) patients respectively. After adjustment, age >75 years, poor blood pressure control were inversely associated with ABC adherent whereas optimal TTR was associated with ABC adherent. There were 7 cases of TE and 9 all-cause mortality during follow up. Conclusion: The study found suboptimal adherence to the ABC pathway in AF patients with a select few risk factors (optimal TTR), displaying unique relationships between ABC pathway adherence. The study will pave the way for further understanding on how clinicians perceive the recommended ABC pathway.